2019
DOI: 10.9734/jpri/2019/v26i130129
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress of Infertile Couples (Male, Female) and the Factors Affecting It

Abstract: Background and Objectives: In addition to physical and mental problems caused by perception of being impotent, social reactions in the society, and the economic and emotional burden of medical costs, infertility causes emotions such as fear, depression, guilty conscience, denial and uncertainty about the future. Methods: This cross-sectional study was conducted on 560 infertile couples referring to the Kurdistan Infertility Diagnosis and Therapeutic Center in 1397. Data were collected using a demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…But on the other hand, men are just like women, and they may be physically and psychologically damaged by various fertility treatments. Mirzaei et al [5] found that the perceived stress in men was higher than the women.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…But on the other hand, men are just like women, and they may be physically and psychologically damaged by various fertility treatments. Mirzaei et al [5] found that the perceived stress in men was higher than the women.…”
Section: Introductionmentioning
confidence: 98%
“…According to worldwide reports, approximately 15% of the married couples are unable to bear any children [4]. Prevalence of infertility is estimated by 9% in the United States, 8.5% in Canada, 10-15% in the Middle East, and by 21.6% in Iran [5].…”
Section: Introductionmentioning
confidence: 99%